Fenomena Living Islam dalam Sinetron - Muh Alwi HS; Amrina Rosyada (MAGHZA, 2018)
This paper presents various forms of Islamic living (Al-Qur'an and Hadith) contained in the Para Pencari Tuhan sinetron, especially in volume 3 episodes 19. This departs from the assumption that every behavior of Muslims is born with understanding (both textual and contextual ) to religious texts, namely the Qur'an and Hadith, including various scenes displayed in the soap opera. Furthermore, as the focus of the study, this paper discusses the issue of love directed at marriage, both experienced by Azam and Aya, Chelsea and Marni, Barong and Dara, as well as scenes of other people who want to involve themselves in the matter. Finally, this paper presents various Islamic living contained in the Para Pencari Tuhan sinetrons, including the Hadith about fasting for Allah, Hadith about the privileges of Khadijah, Hadith about the criteria of the couple to be chosen, Hadith about the prohibition of approaching women being applied, Hadith about orders married to capable young people, verses on polygamy, verses about the importance of the attitude of tabayyun, verses about help, verses about the benefits of marriage. Various hadiths and verses recorded in the form of scenes in soap operas show that films (soap operas) always have a significant role in broadcasting Islamic teachings.